The value of looking ahead: Comparing conventional and strategic Mountain Pine Beetle (Dendroctonus ponderosae) management policies in North America - Emma J. Hudgins; Rory McIntosh; Mike Undershultz; Chris J. K. MacQuarrie; Devin Goodsman; Denys Yemshanov (PLoS ONE, 2026)
Forest management in North American montane and boreal biomes is facing multiple challenges, including climate change, wildfires and pest outbreaks. Mountain pine beetle (MPB, Dendroctonus ponderosae ) is a notable example of a major threat to forest health in western North America whose impacts are compounded by warmer winters, which allowed it to establish further north and east of its historical distributional range. In western Canada, delimiting surveys and control of range-expanding MPB populations are managed through collaborative intergovernmental initiatives. While this approach has been shown to effectively slow MPB spread, these management efforts were planned without assessments of the long-term impacts of survey and control decisions on future rates of MPB spread. Here, we compared the current approach to managing MPB populations driven by recent detections and short-term forecasts against an optimisation-assisted approach that finds a MPB management strategy by factoring in the long-term impacts of survey and management decisions on future spread. We also evaluated a reduced-complexity approach where MPB spread forecasts are factored into decisions without tracking the long-term impacts from future management actions. We found that strategic long-term management could help reduce the future MPB-infested area by 65%−112% compared to the current short-term management strategy. Also, the reduced-complexity approach helped reduce the MPB-invaded area by 16%−77% compared to the conventional short-sighted approach. These results demonstrate the substantial benefits of incorporating longer-term pest spread forecasts and feedback from future management decisions into spatial prioritisations of MPB management efforts.